Influence of the tactical formation on serve and follow-through parameters in professional padel - Iván Martín-Miguel; Bernardino Javier Sánchez-Alcaraz; Jesús Ramón-Llín; Diego Muñoz (Asociación Española de Ciencias del Deporte, 2024)
The aim were to analyse the effect of the tactical formation of the serving pair on serving and follow-through parameters in professional padel. 1089 points distributed in 217  men's matches (19 sets), corresponding to 8 matches of the World Padel Tour circuit played in 2020, were analysed by systematic observation. The results show that from the left side (p=0.002), in both formation the side wall is the predominant direction and independently of the player serving (p<0.05). From the right side (p=0.000), when the server is the player on the right (p=0.008) in conventional, looks for the side wall in more occasions and when it is the player on the left (p=0.000) in Australian, the "T" is the predominant direction. Regardless of the side and player serving, when conventional was used, the direction of the squeeze was side wall more than 66% of the time. Finally, there are also significant differences (p<0.05) depending on the second shot after the return, with the exception of the smash (p>0.05), being the backhand volley the predominant one in both tactical situations. In conclusion, the serving situation influences the tactical parameters of the serve and return allowing the creation of specific strategies during the game.